2014
DOI: 10.1136/bmjopen-2014-005635
|View full text |Cite
|
Sign up to set email alerts
|

Short-term use of remifentanil during endotracheal extubation for prophylactic analgesia in neurosurgical patients after craniotomy (SURE after Craniotomy Study): a study protocol and statistical analysis plan for a randomised controlled trial

Abstract: IntroductionAcute pain is common during the endotracheal extubation period, and is related to complications and adverse outcomes. Patients with delayed extubation after craniotomy are vulnerable to pain and complications of extubation. However, pain control during extubation is still inadequate. Remifentanil, a new opioid with rapid onset and short duration of action, provides adequate analgesia during procedures with minimal effect of respiratory depression.Methods and analysisThe study is a prospective, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, the dosage of propofol, which could provide effective sedation and hypnosis for tolerance endotracheal tube and have little effect on hemodynamic responses, is far below the above usage. Remifentanil, a potent synthetic selective μ-opioid receptor agonist with a rapid onset and short duration of action, can provide sedation and analgesia during the placement of the endotracheal tube, and can cause blunt reflex responses (21). Lee et al reported that the infusion of 1 μg/kg remifentanil, which is in accordance with ours, could lead to a decrease in blood pressure and HR in an acceptable safely range (22).…”
Section: Discussionsupporting
confidence: 78%
“…However, the dosage of propofol, which could provide effective sedation and hypnosis for tolerance endotracheal tube and have little effect on hemodynamic responses, is far below the above usage. Remifentanil, a potent synthetic selective μ-opioid receptor agonist with a rapid onset and short duration of action, can provide sedation and analgesia during the placement of the endotracheal tube, and can cause blunt reflex responses (21). Lee et al reported that the infusion of 1 μg/kg remifentanil, which is in accordance with ours, could lead to a decrease in blood pressure and HR in an acceptable safely range (22).…”
Section: Discussionsupporting
confidence: 78%
“…Prophylactic analgesia is a form of analgesia that blocks the transmission, conduction, and establishment of peripheral injurious impulses to the center and reduces the peripheral and central sensitization caused by noxious stimulus afferents[ 20 ]. As a long-acting, non-accumulative opioid, oxycodone can provide suitable prophylactic analgesia.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…After completing the SBT, patients were disconnected from the ventilator, either breathing through a T-tube circuit with humidified oxygen or extubated as decided by the clinical team using a screen checklist (Table S2) (36,37). Reconnection to the ventilator support was solely decided by the clinical team, who were unaware of the physiological (36).…”
Section: Study Protocolmentioning
confidence: 99%
“…After completing the SBT, patients were disconnected from the ventilator, either breathing through a T-tube circuit with humidified oxygen or extubated as decided by the clinical team using a screen checklist (Table S2) (36,37). Reconnection to the ventilator support was solely decided by the clinical team, who were unaware of the physiological (36). Failed ventilator liberation was defined as the need for invasive ventilator support within 48 h after the SBT, independent of the presence of an artificial airway (tracheostomy or endotracheal tube).…”
Section: Study Protocolmentioning
confidence: 99%